The implications of Irish Home Rule for the British Constitution 1880-1914. - G. Elaine Goldup (2002)
This thesis examines aspects of the 'Irish Question' and its impact on British politics predominantly between 1880 - 1914, with special reference to its implications for the character of the British Constitution, and its efficacy when applied to a divided society. It analyses the conceptual ideas of the major political actors and how these were formulated and adapted to meet particular circumstances. It is divided into five Chapters: 1. Outlines the historical background from the beginning of the seventeenth century to the granting of Catholic Emancipation in 1828. It sets out the makings of a divided society, with particular attention to the plantation of Ulster 2. Examines the arguments for and against the granting of Home Rule during the time of the first and second Home Rule Bills of 1886 and 1893, assessing the strategies used by both the Irish Parties to attain what each perceived to be justice for Ireland. It looks at how successful Gladstone's Governments were at accommodating these two different perceptions of justice. 3. Discusses the evolutionary changes of the British Constitution, with particular attention to the 1911 Parliament Act, examining the Unionists' claim, that the passing of this Act was part of a 'corrupt parliamentary bargain' between the Liberal Government and the Irish Parliamentary Party. 4. Examines A V Dicey's argument that the passing of a Home Rule Bill by virtue of the 1911 Parliament Act would lack constitutional validity, since there were reasonable grounds to suspect that the House of Commons did not represent the determined will of the nation. Hence, the Liberals were usurping the Sovereignty of the people. 5. Assesses Dicey's arguments within the context of the 'Ulster Crisis' 1912-1914, and explores the argument that the passing of Home Rule by virtue of the 1911 Parliament Act would exceed the bounds of legitimate government authority.